Pollock avoided hydrodynamic instabilities to paint with his dripping technique - Palacios, Bernardo; Rosario, Alfonso; Wilhelmus, Monica M.; Zetina, Sandra; Zenit, Roberto (PLOS ONE, 2019)
Jackson Pollock’s most celebrated abstract paintings were produced with the so-called dripping technique. By pouring liquid paint with the help of a stick or from a can, Pollock deposited viscous fluid filaments on a horizontal canvas, rhythmically moving around it. The intricate webs of lines, ubiquitous in his compositions, have fascinated art historians and scientists. Based on image analysis of historical video recordings, we experimentally reproduced the painting process. We conclude that Pollock avoided the appearance of the hydrodynamic instabilities, contrary to what was argued by previous studies. Pollock selected the physical properties of the paint to prevent filament fragmentation before deposition, and applied it while moving his hand sufficiently fast and at certain heights to avoid fluid filaments from coiling into themselves. An understanding of the physical conditions at which these patterns were created is important to further art research and it can be used as a tool in the authentication of paintings.